How Not to Read Philosophical Investigations: McDowell and Goldfarb on Wittgenstein on Understanding. (14th July 2014) - Brandt, Stefan
Abstract In a recent article, John McDowell has criticised Warren Goldfarb for attributing an anti‐realist conception of linguistic understanding to Wittgenstein. 1 I argue that McDowell is right to reject Goldfarb's anti‐ realism, but does so for the wrong reasons. I show that both Goldfarb's and McDowell's interpretations are vitiated by the fact that they do not pay attention to Wittgenstein's positive claims about understanding, in particular his claim that understanding is a kind of ability. The cause of this oversight lies in their endorsement of an excessively anti‐systematic or "therapeutic" reading of Wittgenstein.